Spatial Prioritization for Ecotourism through Applying the Landscape Resilience Model - Shekoufeh Nematollahi; Sadaf Afghari; Felix Kienast; Sima Fakheran (Land, 2022)
Given the growing universal demand for sustainable development in recent years, ecotourism has become one of the top effectual actions that can be employed to reconcile environmental conservation with economic growth. Therefore, sustainable development can be supported by assessing ecotourism ecosystem services at the landscape scale. In this regard, we presented a new technique that considers a potential model of ecotourism along with a landscape resilience measurement to identify the priority areas for sustainable ecotourism development. For this purpose, a multi-criteria fuzzy model with a geographic information system (GIS) and analytical hierarchy process (AHP) was first used to evaluate potential zones for ecotourism. The landscape ecological risk index (ERI) was then applied to measure the landscape resilience. The usefulness of our novel technique was then tested in a case study in the Chaharmahal and Bakhtiari province (Ch & B), situated in the central part of the Zagros Mountain Chains, Iran. The area has a coarse terrain with climate that varies considerably, which results in high potential for ecotourism development. The results indicated that about half of the provincial area had high potential for developing ecotourism and attracting tourists. However, when considering the landscape resilience, approximately 33% of the study area near the western and central regions had both high potential for ecotourism and the high values of landscape resilience, making these locations suitable for sustainable ecotourism development. Overall, the present study demonstrated that utilizing the integrated models and the ecotourism potential model, together with the landscape resilience assessment, might provide a powerful tool for ecotourism prioritization for the purpose of sustainable development.